Central Nervous System Complications in HIV Disease: HIV-Associated Neurocognitive Disorder - Letendre, Scott (Top Antivir Med, 2016)
HIV-associated neurocognitive disorder (HAND) is the result of neural damage caused by HIV replication and immune activation. Potent antiretroviral therapy has reduced the prevalence of severe HAND but not mild to moderate HAND. Brief symptom questionnaires, screening tests, and neuropsychological tests can be used with relative ease in the clinic to identify cognitive and neurologic deficits and to track patient status. Increasing data on pharmacokinetics of antiretrovirals in cerebrospinal fluid (CSF) have permitted formulation of central nervous system (CNS) penetration-effectiveness (CPE) rankings for single drugs and combinations. Available data indicate that regimens with higher CPE scores are associated with lower HIV RNA levels in CSF and improvement in neurocognitive functioning. This article summarizes a presentation by Scott Letendre, MD, at the IAS–USA live continuing medical education course held in San Francisco in May 2011.